Strategi Pemasaran dan Tantangan Penjualan di Era Digitalisasi : Studi Kasus UMKM Cemilan Keripik Tempe Kenzi di Jl. Danau Maninjau LK. IV Kelurahan Padang Merbau Kota Tebing Tinggi - Aziti, Tria Meisya; Saragih, Linda Hertaty; Wirdayanti, Wirdayanti (Community Service Progress, 2025)
This study aims to analyze and propose effective digital marketing strategies for tempeh producers, who often still rely on traditional marketing methods, and to help MSMEs adapt to changing consumer behavior in the digital era. Tempeh product marketing strategies in the digital era generally discuss the importance of adopting digital technology by tempeh Micro, Small, and Medium Enterprises (MSMEs) to expand market reach and increase competitiveness. It also identifies various sales strategies and challenges they face.